(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article examines communicative and modern methods of teaching English. It highlights the importance of fostering real-life communication skills and integrating contemporary teaching techniques to enhance language acquisition. Key approaches discussed include task-based learning, technology integration, and student-centered methodologies. The goal is to create engaging and effective learning environments that cater to the needs of today’s learners.